Interdisciplinaridade e aprendizagem significativa no contexto da educação profissional e tecnológica do estado do Paraná - Rocha, Marcia Oliveira (2017)
The interdisciplinary practice in teaching work comprises a didactic make centerd on reflection on the teacher's activities in the framework of methodologies, in commitment to the learning of their students, the ability to become, in solidarity, and, consequently, be an employee in training psycho-affective and social development of learners. This is particularly a challenging attitude of the teacher, therefore, involves reflection and resumed, research, changes of paradigms and teach in addition to the new technologies, which means: a sensitive look on the human and humanising activity essentially the act of teaching. When we refer to "sensitive look”, treat the interdisciplinary didactic approach focused on students' learning with meaning, and under this approach, the theme of this research has as objective to investigate the contribution of interdisciplinary practice teaching, as propelling tool of meaningful learning in students of a school teaching vocacional education a state school in the city of Curitiba/PR. The research was composed by two moments: the first, documentary and bibliographic and subsequently, the field research based on the phenomenological qualitative research approach in a state school of Education in the municipality of Curitiba, students, teachers and pedagogical coordinator participated in this work. In the initial chapter, studies have understood the Legal aspects of the Technical Course of medium level security of the work and the nature of teaching in Vocational and Technological Education. In the second chapter, the training of teachers in the context of interdisciplinarity, the curriculum and pedagogical practice and meaningful learning by the prospect of David Ausubel and Joseph Novak and Bob Gowin. The third chapter presents the research and interpretation of the data obtained in the light of the theoretical assumptions for this work. It is emphasized, therefore, that this research underscores the triad of meaningful learning - interdisciplinary faculty-posture affectivity-learn with meaning